Phase equilibria of Ti–Al–V system at 1300 °C. (December 2019) - Zhang, Heng; Lin, Junpin; Liang, Yongfeng; Xu, Shuai; Xu, Yong; Shang, Shun-Li; Liu, Zi-Kui
Abstract: Phase equilibria in the Ti–Al–V system at 1300 °C were studied experimentally by examining 50 samples with compositions up to 75 at % Al. An isothermal section of Ti–Al–V at 1300 °C was constructed by means of X-ray diffraction (XRD), electron backscattered diffraction (EBSD), scanning electron microscopy (SEM), and electron probe microanalysis (EPMA). The isothermal section is characterized by five single-phase regions (i.e., α phase with hcp_A3 structure, β phase with bcc_A2 structure, γ phase with L10 structure, δ phase with D82 structure, and ε phase with D022 structure) and three three-phase regions (α+γ+ε, α+δ+ε, and α+β+δ). Compared with the tentative results at 1200 °C, the single α phase at 1300 °C is highly extended, while the other single-phase regions remain almost unchanged, resulting in the emergence of new three-phase regions. Graphical abstract: Image 1 Highlights: An isothermal section in Ti–Al–V system at 1300 °C is established. The α single phase region is in substantial enlargement at elevated temperature which has not been reported in this system. Abundant experimental statistics possibly provided for modeling are obtained. New three-phase regions are found and the possible invariant reaction are proposed.